Direct and Single‐Molecule Visualization of the Solution‐State Structures of G‐Hairpin and G‐Triplex Intermediates1. (12th March 2014) - Rajendran, Arivazhagan; Endo, Masayuki; Hidaka, Kumi; Sugiyama, Hiroshi
Abstract We present the direct and single‐molecule visualization of the in‐pathway intermediates of the G‐quadruplex folding that have been inaccessible by any experimental method employed to date. Using DNA origami as a novel tool for the structural control and high‐speed atomic force microscopy (HS‐AFM) for direct visualization, we captured images of the unprecedented solution‐state structures of a tetramolecular antiparallel and (3+1)‐type G‐quadruplex intermediates, such as G‐hairpin and G‐triplex, with nanometer precision. No such structural information was reported previously with any direct or indirect technique, solution or solid‐state, single‐molecule or bulk studies, and at any resolution. Based on our results, we proposed a folding mechanism of these G‐quadruplexes.